Fak‐Mapk, Hippo and Wnt signalling pathway expression and regulation in distraction osteogenesis. (5th March 2018) - Song, Jian; Ye, Bin; Liu, Hanghang; Bi, Ruiye; Zhang, Nian; Hu, Jing; Luo, En
Abstract: Objectives: To investigate the mechanism of mechanical stimulation in bone formation and regeneration during distraction osteogenesis. Materials and methods: In this study, microarray technology was used to investigate the time course of bone‐related molecular changes in distraction osteogenesis in rats. Real‐time PCR and Western‐blot analyses were used to confirm the expression of genes identified in microarrays. Meanwhile, we used a lentivirus vector to inhibit Fak expression, in order to identify the osteogenic effect of Fak and Fak‐Mapk pathway during distraction osteogenesis. Results: Several components of the Wnt and Hippo pathways were found to be up‐ or down‐regulated during distraction osteogenesis by microarray. Meanwhile, it was found that Fak, Src, Raf‐1, Erk1, Jnk and p38‐Mapk were up‐regulated during gradual distraction, compared with consolidation. To further determine whether Fak‐Mapk pathway played an important role in distraction osteogenesis, Fak was disrupted with a lentivirus vector. The expressions levels of p‐Fak, p‐Erk1/2, p‐JNK and p‐p38Mapk were decreased. Meanwhile, a poor early and late osteogenesis effect was found in the shRNA‐Fak group. Conclusion: It was inferred that the mechanical stimulus induces increased expression of Fak and activates Fak‐Mapk pathway, by activation of Erk, Jnk and p38‐Mapk pathway, and that Fak at least, in part, plays an important role in maintaining osteogenic effect by activating Fak‐Mapk pathway during distraction osteogenesis.